Diffusion-weighted MR imaging findings in an isolated abscess of the clivus - Soares-Fernandes, JP (2012)
We report the finding of restricted diffusion in an isolated abscess of the clivus and discuss the imaging differential diagnosis, with an emphasis on the usefulness of diffusion-weighted imaging.